Genesis of the South Zhuguang Uranium Ore Field, South China: Pb Isotopic Compositions and Mineralization Ages. Issue 1 (20th July 2018) - Zhang, Chuang; Cai, Yuqi; Dong, Qian; Xu, Hao
Abstract: U–Pb isotopic analyses indicate that ores from the South Zhuguang uranium ore field, south China, have high common (non‐radiogenic) Pb contents, with variable and relatively radiogenic initial Pb contents. The U–Pb isochron method was used to date these ores, with plots of 208 Pb/ 204 Pb and 207 Pb/ 204 Pb versus 206 Pb/ 204 Pb being used to identify sample suites with similar initial Pb isotopic ratios and to normalize variable initial Pb isotopic ratios. The resulting U–Pb isochrons indicate two substages of uranium mineralization at 57 and 52 Ma, with a later hydrothermal reformation at 49 Ma, which homogenized Pb isotopic compositions. Initial Pb isotopic systematics indicate that the ore‐forming fluid was characterized by high 206 Pb/ 204 Pb and 207 Pb/ 204 Pb ratios and low 208 Pb/ 204 Pb ratios, suggesting that the ore‐forming fluid was sourced from Cretaceous–Paleogene red‐bed basins, rather than from magma or the mantle, with consideration of mineralization ages. Abstract : This paper mainly focuses on the genesis of South Zhuguang Uranium Ore Field. Through the U‐Pb dating of pitchblende and syn‐ore pyrites, we outlined the mineralization ages of different stages, and the evolution of Pb isotopes, ultimately proposed ore‐forming fluid sourced from Cretaceous‐Paleogene redbed basins in the South.